1989
DOI: 10.1111/j.1532-5415.1989.tb05868.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Disturbance, Cognitive Dysfunction, and Functional Skill

Abstract: The nature and severity of behavioral problems, and their relationship to cognitive and functional abilities, was investigated in 56 community‐residing patients with Alzheimer's disease. Measures evaluated three domains of function: behavior, cognition and activities of daily living. Problems of cognitive functioning, such as memory loss, confusion, and disorientation were most prevalent, reported to occur in 84%, 82%, and 64% of the sample, respectively. Problems with activity and emotional distress were next… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(15 citation statements)
references
References 26 publications
1
12
0
1
Order By: Relevance
“…In the present study vegetative disorders were found in up to 84% of the patients. Sleep disturbance has been reported to be present in up to 45% of patients with dementia5#l6 and incontinence in 17% of o~tpatients.~, 21 Restless sleep was the most common single disturbance in our outpatient sample, occurring in nearly 40% of patients. Incontinence was present in just over a fifth of the outpatients.…”
Section: Discussionmentioning
confidence: 63%
“…In the present study vegetative disorders were found in up to 84% of the patients. Sleep disturbance has been reported to be present in up to 45% of patients with dementia5#l6 and incontinence in 17% of o~tpatients.~, 21 Restless sleep was the most common single disturbance in our outpatient sample, occurring in nearly 40% of patients. Incontinence was present in just over a fifth of the outpatients.…”
Section: Discussionmentioning
confidence: 63%
“…Other studies have suggested that violence is the one behavioral problem that is most likely to worsen with increasing severity of dementia (Petry et al, 1988;Swearer et al, 1988). Using information from physicianevaluations, Teri et al (1988) found that incontinence, poor hygiene, agitation, and wandering increased with increasing cognitive impairment, but were unable to replicate these findings when a caregiver checklist method was used (Ten et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…We gratefully acknowledge the contributions of our project staff, mcludmg Meredith Pfanschmidt, Zilpha Haycox, Sheila O'Connell, Duane Beekly, and Ross Barnhart Portions of this paper were presented at the Amencan Geriatrics Society and American Federation for Agmg Research Annual Meeting, May [6][7][8][9][10] 1998, Seattle, WA…”
Section: Acknowledgmentsmentioning
confidence: 99%